8B.04: RENAL ARTERY DENERVATION FOR TREATMENT OF HYPERTENSIVE PATIENTS WITH OR WITHOUT OBSTRUCTIVE SLEEP APNEA AND RESISTANT HYPERTENSION. (June 2015) - Mahfoud, F.; Linz, D.; Mancia, G.; Narkiewicz, K.; Ruilope, L. M.; Schlaich, M. P.; Schmieder, R. E.; Williams, B.; Böhm, M.
Abstract : Objective: Obstructive sleep apnea (OSA) is associated with sympathetic nervous system activation and the development of hypertension. The Global SYMPLICITY Registry is prospectively enrolling real world patients with uncontrolled hypertension including patients with OSA. This analysis compares baseline characteristics and blood pressure (BP) lowering effects of renal denervation in patients with and without OSA. Design and method: The Global SYMPL CITY Registry is a prospective, multicentre international registry designed to evaluate the safety and effectiveness of renal denervation in a broad population of patients with uncontrolled hypertension. Baseline characteristics antihypertensive medication use, office and 24-hour ambulatory BP are compared between patients with and without OSA. Results: In a 998 patients with complete 6 month follow-up OSA was reported in 116 patients. OSA patients were more likely to be male than patients without OSA (n = 752) (83% vs 56%, p < 0.0001), had a larger body mass index (34 ± 6 kg/m2 vs 30 ± 5 kg/m2, p < 0.0001) and significantly more, left ventricular hypertrophy (25% vs 15%, p = 0.008) atrial fibrillation (19% vs 11%, p = 0.020) and diabetes (52% vs 39%, p = 0.008). OSA patients were taking more antihypertensive medications (4.9 ± 1.4 vs 4.4 ± 1.3, p < 0.001); a higher proportion of aldosterone antagonists (39% vs 20%, p < 0.0001), vasodilators (24% vs 13%, p = 0.001) and alpha 2 agonists (54% vs 36%, p < 0.001). Baseline office systolic BP was 166 ± 23 mm Hg for OSA patients and 163 ± 24 mm Hg for non-OSA patients. At 6 months the office systolic BP was reduced -15.5 ± 24.4 mm Hg in the OSA group and -11.3 ± 25.0 mm Hg in the non-OSA group (both p < 0.0001; p = 0.136 for difference between the groups). Baseline ambulatory 24-hr systolic BP was 156 ± 20 mm Hg in OSA patients and 152 ± 17 in non-OSA patients. At 6 months 24-hour systolic BP declined -4.6 ± 17.1 mm Hg (n = 73, p = 0.023) in the OSA group and -7.1 ± 17.6 mm Hg (p < 0.0001) in the non-OSA group (p = 0.450 for the between group difference). Conclusions: Renal denervation resulted in significant 6-month BP reductions in patients with and without OSA but there was not a significant difference in the BP change between the 2 groups. Data from a larger cohort of 2100 patients will be presented.